My life is murder. Series 2 [videorecording (DVD)]. - Lawless, Lucy, 1968-; Vagulans, Ebony; Curry, Bernard, 1974-; Andreas, Alex; Jobe, Rawiri; Naufahu, Joe (Acorn Media, 2021)
When determined detective Alexa Crowe brings her unique brand of investigation to an unsuspecting New Zealand, My Life Is Murder returns bigger than ever, building on the warmth, intrigue, humor and charm of its Australian series. Alexa quickly finds herself entangled in compelling new murder mysteries centered on fascinating and dangerous characters who will challenge, flirt with and frustrate her, and sometimes threaten everything she cares about. There may be new friends and locations to explore but Alexa's life is still very much murder. She's ready to use her powers for good and bring her always surprising sleuthing style back at full force.